Viabilidade e vigor de sementes florestais pelo teste de Tetrazólio - Pereira, Kleane Targino Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
The tetrazolium test is a rapid method to assess the viability and vigor. However, some factors, such as seed dressing, concentration of the tetrazolium salt solution and the time of exposure, may interfere with the efficiency of the test. The objective of this study was to determine the appropriate tetrazolium test methodology for evaluating the viability and vigor of seeds of the species Anadenanthera colubrina var. Cebil (Griseb.) Altshul and Piptadenia stipulacea (Benth.) Ducke. The research was carried out in three stages, the first being the initial quality of the seeds, through germination, emergency, germination speed index and emergency speed index, the germination and emergency germination time. Then, in second step, the imbibition curve was perfomed to define the seed hydration time. The seed preparation mode for the tetrazolium test was also determined by testing hydration periods, tetrazolium solution concentrations and staining periods. After the choice of the best method of preparation of the seeds for the tetrazolium test, the third stage of the experiment was started, with a completely randomized experimental design, in a 3x9 factorial scheme, three sublots and nine combinations, consisting of three concentrations of the tetrazolium solution and three staining periods, totaling twenty-seven treatments with four replicates of 25 seeds, evaluated separately at 35 and 40 ° C, for each species alone. After each treatment, the seeds were washed, cut longitudinally and separated into the following classes: viable and vigorous (class I), viable and non-vigorous (class II), non-viable (class III) and dead (class IV) seeds. Thus, in the preparation of the seeds, we may conclude that it is necessary to blunt in the region opposite to the micropyle for the two species, with subsequent soaking in water for 10 hours (A. colubrina) and for 8 hours (P. stipulacea) at 25 ° C, followed by removal of the integument before immersion in the tetrazolium salt. The combination that provided the best viability and vigor result was 0.075% for four hours, at 35 ° C for A. colubrina and at 35 e 40 °C for P. stipulacea. Therefore, the tetrazolium test is efficient to evaluate the viability and vigor of seeds of the species analyzed
Keywords: A. colubrina. P. stipulacea; Análise de sementes; Espécies florestais; Qualidade fisiológica; A. colubrina. P. stipulacea; Analysis of seeds; Forest species; Physiological quality; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA